Small-Scale Fishermen's Perceptions of the Use of Information Technology in Livelihood Activities in Pallameang Village, Mattirosompe District, Pinrang Regency - Annisa Maulid Wina; Andi Adri Arief; Muhammad Dalvi Mustafa; Andi Amri (PONGGAWA : Journal of Fisheries Socio-Economic, 2026)
This study aims to determine the type of information technology used and the perception of small-scale fishermen towards its use in livelihood activities in Pallameang Village, Mattirosompe District, Pinrang Regency. The study was conducted in January–February 2025 using a mix method approach, namely a combination of qualitative and quantitative methods. The number of samples of 30 fishermen was determined through cluster random sampling techniques. Primary data were obtained through observation, in-depth interviews, and questionnaires, while secondary data were obtained from documents and literature studies. Data analysis was carried out descriptively and using a Likert scale to measure the level of perception. The results showed that the type of information technology most widely used by fishermen was mobile phones (100%) as the main communication tool, followed by GPS (67%) which was used to determine fishing locations. The Windy application is used by 27% of respondents, the Asia & Africa HD application by 10%, while the compass is only used by 7% of respondents. Fishermen's perception of the use of information technology in fishing activities is very good, but its use in marketing the catch is still relatively low. The obstacles faced by fishermen include limited costs, limited internet networks, and low digital literacy. However, all fishermen stated that they strongly agree and are interested in participating in training related to information technology. Therefore, support from various parties is needed to improve access and skills in information technology for fishermen in order to support their work efficiency and welfare in a sustainable manner.